2015
DOI: 10.1109/tim.2014.2359812
|View full text |Cite
|
Sign up to set email alerts
|

On the Calibration of Direct-Current Current Transformers (DCCT)

Abstract: Modern commercial direct-current current transformers (DCCT) can measure currents up to the kA range with accuracies better than 1 × 10 −5 . We discuss here a DCCT calibration method and its implementation with commercial instruments typically employed in low resistance calibration laboratories. The primary current ranges up to 2 kA; in the current range below 100 A the calibration uncertainty is better than 3 × 10 −7 . An example of calibration of a high-performance DCCT specified for primary currents measure… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 13 publications
0
7
0
Order By: Relevance
“…For example, [ 25 , 26 ] present a calibration system for ITs. In [ 27 ], the authors studied the calibration of direct current (DC) current transformers (CT); while in [ 28 ] it was conducted for digital ITs. A calibration procedure for legacy CTs was presented in [ 29 ], while different kinds of LPITs were calibrated in [ 30 , 31 , 32 ].…”
Section: Importance Of Testingmentioning
confidence: 99%
“…For example, [ 25 , 26 ] present a calibration system for ITs. In [ 27 ], the authors studied the calibration of direct current (DC) current transformers (CT); while in [ 28 ] it was conducted for digital ITs. A calibration procedure for legacy CTs was presented in [ 29 ], while different kinds of LPITs were calibrated in [ 30 , 31 , 32 ].…”
Section: Importance Of Testingmentioning
confidence: 99%
“…The error of the DC ITTS can be calculated with formula (2). Considering the error of the signal source, the DC micro-difference device and digital multimeter, the calculation formula of the DC ITTS's error can be modified from formula (2) to formula (8).…”
Section: Calibration Test Of the DC Ittsmentioning
confidence: 99%
“…As the dependence of the second harmonic component voltage on the DC current is non-linear, fluxgate current sensors usually work in the feedback loop compensating the measured DC current to zero. These sensors are also called DC current transformers [72], [73], [74]. We have shown that this mechanism can be used on a standard current transformer by injecting the excitation current into the secondary winding [75].…”
Section: Fig 3 Rogowski Coil Integrated Into the Laminated Busbar -Amentioning
confidence: 99%